Effects of Antioxidants (Selenium, Vitamin C and Vitamin E) and Feed Allocation on Broiler Breeder Egg Production, Fertility and Hatchability - Romero-Sanchez, H.; Joardar, D.; Walker, G.K.; Brake, J. (International Journal of Poultry Science, 2020)
Background and Objective: Optimum feed allocation and antioxidant levels are important for sustained fertility of broiler breeder flocks. This study investigated effects of different antioxidant sources and levels on male fertility. Materials and Methods: In Experiment 1, males were divided assigned to a large comb (LC) or small comb (SC) height group at 20 week and fed a layer diet with either organic high selenium yeast [(HiSe Yeast) Selplex®] or inorganic selenium [sodium selenite (NaSe)]. In Experiment 2, all birds were randomly assigned to receive a High (Vitamins C, E and HiSe) or Normal antioxidant layer diet. Results: Experiment 1: LC males receiving NaSe exhibited reduced fertility that was related to a significantly heavier BW relative to the feed allocation. Similarly, the SC males that received more ME relative to BW responded with improved fertility but significantly increased BW at 40 week of age. An interaction between comb size and selenium source suggested that when higher BW males (LC) were underfed, the HiSe Yeast maintained high fertility irrespective of gain in BW. Experiment 2: Overall, High antioxidant levels increased fertility. Further, after 38 week of age, there was a decrease in fertility due to an inadequate feed allocation for males that had a reduced effect on the High antioxidant group. However, when male feed allocation was increased at 54 week of age the differences due to antioxidant level were diminished. Conclusion: Consistent feed increments that maintained a consistent male BW gain and elevated antioxidant levels is important for maintaining fertility.